The Effects of Chewing Gum on the Formation of Plaque on the Smooth Teeth Surface - F Vaziri; M Kamaladdini (Islamic Azad University, 2022)
Background and objectives: Gingivitis is the most common gingival inflammatory disease. Plaque control methods play a major role in the prevention of periodontal disease and dental caries, which include mechanical and chemical technique. The present study was conducted to investigate the effect of chewing gum on dental plaque on smooth teeth surface. Methods: A cross-over clinical trial was conducted on 18 subjects. The study was conducted in two 2-day duration with a 4-day wash out period. At the beginning of the study, subjects received professional prophylaxis. During the study period, they refused to brush and floss. Volunteers in the test group were instructed to chew one pellet four times a day for 20 min. On the third day, O'Leary and the Bleeding Point Index were measured. In the second stage, two groups were displaced. Finally, the data were subjected to statistical analysis by paired t-test and Wilcoxon. Results: There was no significant reduction in plaque and bleeding index in test group (P =0.187) compared to control group. Conclusion: In the absence of oral health procedure, chewing gum has no significant effect on plaque reduction in the smooth teeth surface.